Proses Penanganan Rel Aus Pada Lengkung NO.16A KM 4+8/0 Jalur Hilir Lintas Manggarai – Tanah Abang - Pamursari, Nurmagita; Fadhilah, Muhamad Farras; Sari, Nurwanda (PendIPA Journal of Science Education, 2025)
Railways is a unified system consisting of infrastructure, facilities, and human resources, as well as norms, criteria, requirements and procedures for the implementation of railway transportation. Railroad infrastructure is a railway line, train stations and train operating facilities. Railway maintenance activities are preventive measures (preventive) and / or replacement in accordance with the technical age. In this study there are several types of maintenance in handling rail replacement on the Manggarai - Tanah Abang crossing. From this study the total wear that occurred from KM 4+800 to 5+00 reached 232.2 meters of track. Wear occurs in curve number 16A. Then there are several treatments carried out such as checking rail material data, replacing rail roads, maintaining forces and electricity, normalizing arrows, and thermite welding. In this rail replacement, maintenance is carried out by inspecting the railroad, maintaining the lighting force whose height must be adjusted to the radius of the curve, and returning the arrows which require prior calculation in carrying out maintenance. Calculation of arrows and elevation must be in accordance with applicable regulations or standards.